Antibacterial Effectiveness of Star Anise Extract (Illicium verum) Against the Growth of Klebsiella pneumoniae ESBL - Andi Muhammad Alif; Marzelina Karim; Andy Visi Kartika; Yani Sodiqah; Rachmat Faisal Syamsu (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Klebsiella pneumoniae is an opportunistic pathogen with high antibiotic resistance, posing significant treatment challenges. Star anise (Illicium verum) contains bioactive compounds like shikimic acid and anethole, which exhibit antibacterial potential. However, its effectiveness against Klebsiella pneumoniae remains underexplored. This study aimed to evaluate the antibacterial efficacy of star anise extract against Klebsiella pneumoniae and compare it with meropenem as a positive control. This in vitro experimental study employed the Kirby–Bauer disc method with a post-test-only control group design. Star anise extract was prepared via maceration and tested at concentrations of 20%, 40%, 60%, 80%, and 100%. Phytochemical tests identified active compounds, while Klebsiella pneumoniae was confirmed through biochemical tests and Gram staining. Antibacterial effectiveness was assessed based on inhibition zone diameters on Mueller Hinton agar. Data were analyzed using one-way ANOVA at a 95% significance level. The extract contained saponins, alkaloids, flavonoids, tannins, and trans-anethole. While increasing extract concentration significantly enhanced the inhibition zone diameter (p < 0.05), all concentrations were categorized as weak against Klebsiella pneumoniae. Based on the diameter of the inhibition zones, the antibacterial activity of the star anise extract against Klebsiella pneumoniae can be classified as weak, particularly against resistant strains.